STUDYING EMOTIONS IN LITERARY DISCOURSE: APPLICATION TO EMOTIONAL ANALYSIS IN THE STRANGER AND THE PLAGUE BY ALBERT CAMUS - Phuong Lan, Le Thi (VNU Journal of Foreign Studies, 2021)
This article aims to point out that the study of emotions in literary works is an intersection of discursive research in literature and in linguistics. We rely on characteristics of the genre, the writer's style, the philosophy of the work to understand the emotions expressed by the narrator and the character. Basing on that, the study identifies the means of expressing emotions used in the work. In the theoretical part, we present directions to study emotions in discourse, characteristic of fictional discourse, and clarify the connotation of two concepts: ethos and pathos. From that theory, we investigate the emotions that make up the irrational sentiment in The Stranger and the rebellious sentiment in The Plague as well as identify the means of expressing the two emotions above. The comparison of the means of expressing emotions in the two works allows us to understand the worldview and perspective of the writer Albert Camus in the two writing periods that he calls "Absurd period" and "Rebellion period".